IMPLEMENTASI PERATURAN WALIKOTA PARIAMAN NOMOR 27 TAHUN 2020 TENTANG PEDOMAN TATANAN NORMAL BARU PRODUKTIF DAN AMAN CORONA VIRUS DISEASE 2019 DI KOTA PARIAMAN PADA PUSAT KERAMAIAN - Boiziardi AS, Rafika Dian Purissa dan (Normative Jurnal Ilmiah Hukum, 2021)
In general, the implementation of the Mayor of Pariaman Number 27 of 2020 concerning Guidelines for the New Productive and Safe Covid-19 Normal Order in Pariaman City At the Crowd Center has not yet been implemented with the maximum level of awareness and discipline of the community towards the dangers of the Covid-19 virus outbreak is still very low, obstacles in implementation This regulation on the market is still a lack of awareness from the public, Lack of information that is known by traders and visitors about health protocols, as well as market conditions that are difficult to implement health protocols. In minimarkets/supermarkets, business actors intentionally do not implement health protocols and maintain a safe distance when queuing for cashiers. Efforts are being made to overcome obstacles in the market by conducting socialization to the public about the new normal order and Perwako Pariaman, coordinating with related parties in the implementation of health protocols, and taking firm action by providing multilevel sanctions against violators. At minimarkets by recording data and conducting discipline and routinely conducting raids. Therefore, the Covid-19 Task Force team must be even more active in providing socialization, counseling, direction and guidance to traders and buyers and taking firm action against any health protocol violators.